A fuzzy logic based approach for network selection in WLAN/3G heterogeneous network - Abbas, Nadine (2015)
To meet the huge traffic growth, heterogeneous networks composed of wireless local area networks (WLAN) and cellular networks are used to provide higher capacity and coverage. When the two networks are available, switching from one network to the other when downloading data is needed to provide good system performance. This paper proposes a fuzzy logic based approach for an automated network selection based on real-network implementations and measurements. The proposed network selection model is based on fuzzy inference rules considering features that affect the selection decision and are available to the user's device. The model input features are linguistic variables representing the signal strength reflecting the channel quality of WiFi and 3G links and network load. Using fuzzy inference rules, WiFi and cellular data rates are inferred from the fuzzy sets of the input variables. Then, the final network selection decision is either WiFi or cellular link based on the fuzzified WiFi and 3G rates and corresponding if-then inference rules. In addition, the performance of the proposed fuzzy logic approach for real-time network selection is evaluated and shown superior to the use of WiFi and 3G links separately.